Dynamics of Solid Waste Research: A Bibliometric Analysis of Global Scientific Publications - Wulandari, Suci; Erpinda, Mia; Faizaturrohmah, Nur (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
It is projected that global waste production will reach 3.4 billion tons by the year 2050, with 33% of this waste not managed in an environmentally sustainable manner. Since the beginning of the 21st century, there has been a significant increase in household and industrial waste, which poses major environmental, public health, and policy challenges. This study employed a systematic literature review (SLR) approach and bibliometric analysis to map global solid waste research trends. The data were collected in three stages: article identification, eligibility screening, and metadata extraction. These data were then analyzed using VOSviewer 1.6.20. A comparative analysis revealed a paradigm shift from a linear approach towards a circular economy model between 2004 and 2024. The period 2014-2024 signifies the consolidation of the concept of sustainability, marked by a 72% increase in network complexity. The research focus underwent a shift from municipal solid waste management to circular economy systems, which are now linked to 38% more derived concepts. New subjects, such as plastic pollution and post-consumption plastic waste, have emerged as predominant themes in 28% of recent publications. The density visualization demonstrates the most significant concentrations in the domains of circular economy and municipal waste management. There has been a marked increase in research activity in recent years, particularly with respect to plastic pollution and waste valorization.